Negative effects of abuse of laxatives in medical practice - Yu.M. Stepanov; O.N. Vlasova; M.V. Stoikevych (Gastroenterologìa, 2018)
The abuse of laxatives is a disorder characterized by an incomprehensible and changing range of gastrointestinal, electrolytic and acid-base abnormalities that can lead to both the onset of chronic diseases and fatalities. Abuse is self-induced, veiled and associated with psychological abnormalities, making it difficult to diagnose. As a safe laxative drug for patients who need long-term treatment of constipation, the drug EasyDo may be recommended.